2022
DOI: 10.3389/fimmu.2021.823935
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Denervation Ameliorates Renal Fibrosis via Inhibition of Cellular Senescence

Abstract: ObjectiveContinuous overactivation of the renal sympathetic nerve is considered to be an important cause of renal fibrosis. Accumulated senescent cells in the damaged kidney have metabolic activities and secrete amounts of proinflammatory factors as part of the SASP (the senescence-associated secretory phenotype), which induce chronic inflammation and fibrosis. It is still unclear whether renal sympathetic nerves affect renal inflammation and fibrosis by regulating cellular senescence. Therefore, we hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…4,5 Enhanced renal sympathetic nerve traffic has also been implicated in the progression of chronic kidney disease, in part related to the stimulation of intrarenal angiotensin II and in part related to the activation of α-2 adrenoreceptors, which may play a role in the pathogenesis of renal interstitial inflammation and fibrosis. 6,7 Renal denervation produces favorable effects in experimental HF and renal disease and improves cardiac function in the clinical setting. [4][5][6][7][8][9] Of note, although they are generally characterized as inhibitors of the sympathetic nervous system, β-blockers do not reduce renal sympathetic nerve traffic.…”
Section: Potential Actions Of Sglt2 Inhibitors As Nephrocentric Neuro...mentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Enhanced renal sympathetic nerve traffic has also been implicated in the progression of chronic kidney disease, in part related to the stimulation of intrarenal angiotensin II and in part related to the activation of α-2 adrenoreceptors, which may play a role in the pathogenesis of renal interstitial inflammation and fibrosis. 6,7 Renal denervation produces favorable effects in experimental HF and renal disease and improves cardiac function in the clinical setting. [4][5][6][7][8][9] Of note, although they are generally characterized as inhibitors of the sympathetic nervous system, β-blockers do not reduce renal sympathetic nerve traffic.…”
Section: Potential Actions Of Sglt2 Inhibitors As Nephrocentric Neuro...mentioning
confidence: 99%
“…6,7 Renal denervation produces favorable effects in experimental HF and renal disease and improves cardiac function in the clinical setting. [4][5][6][7][8][9] Of note, although they are generally characterized as inhibitors of the sympathetic nervous system, β-blockers do not reduce renal sympathetic nerve traffic. 10…”
Section: Potential Actions Of Sglt2 Inhibitors As Nephrocentric Neuro...mentioning
confidence: 99%
“…Others demonstrated recently that sympathetic denervation led to amelioration of renal fibrosis and of cellular senescence in a model of unilateral ureteral obstruction and a model of unilateral ischemia-reperfusion injury. Interestingly, the cellular senescence of renal proximal tubular epithelial cell lines was mediated by a selective α2A-adrenergic receptor in vitro ( Li et al, 2022 ). These findings provide clues to the possible neurometabolic and neuroimmune mechanisms that could explain the increase of renal collagen due to impaired control of renal sympathetic nerve activity.…”
Section: Discussionmentioning
confidence: 99%
“…These studies emphasize the importance of inflammation microenvironment in cellular senescence. Meanwhile, Qian Li et al pointed out that renal sympathetic neurotransmitter NE, acting on the α 2A -AR of epithelial cells, could promote the crosstalk between inflammation and cellular senescence, contributing to renal fibrosis after IR injury [ 54 ]. Weifeng Yao et al found that aerosol inhalation of a hydrogen-rich solution would attenuate renal macrophage infiltration, the release of pro-inflammatory cytokine, and cellular senescence via TGF-β1 pathway in septic acute kidney injury (AKI) [ 55 ].…”
Section: Recent Advances In Ischemia/reperfusion-induced Senescence M...mentioning
confidence: 99%